2009
DOI: 10.1088/0957-4484/20/42/425201
|View full text |Cite
|
Sign up to set email alerts
|

The size dependence of tin oxide atomic cluster nanowire field effect transistors

Abstract: Tin oxide (SnO(2)) cluster nanowires have been fabricated using atomic clusters as building blocks. Nanowires with widths of less than 100 nm were defined using electron beam lithography followed by deposition of Sn clusters which were subsequently thermally oxidized. The cluster nanowires were used to fabricate field effect transistors. The transistors were n-type and demonstrated a clear size-dependent behaviour. With zero gate bias the narrowest wires were depleted, both the carrier concentration and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…It is now recognized that the distinctly improved properties of nanoscale materials probably derives from their enlarged surface areas and quantum confinement effects. SnO 2 , as one of the most important semiconductive materials, has attracted extensive efforts for various applications in field effect transistors [4,5], solar cells [6,7], gas sensors [8e10], and catalyst supports [11]. Particularly, SnO 2 is a promising anode candidate in lithium ion batteries owing to its theoretical capacity of 782 mAh g À1 which is superior to the currently commercialized graphite (372 mAh g À1 ) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is now recognized that the distinctly improved properties of nanoscale materials probably derives from their enlarged surface areas and quantum confinement effects. SnO 2 , as one of the most important semiconductive materials, has attracted extensive efforts for various applications in field effect transistors [4,5], solar cells [6,7], gas sensors [8e10], and catalyst supports [11]. Particularly, SnO 2 is a promising anode candidate in lithium ion batteries owing to its theoretical capacity of 782 mAh g À1 which is superior to the currently commercialized graphite (372 mAh g À1 ) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the decreasing of total interaction energy well explains the increasing EB value after 30 min annealing, the slight negative chemical shift of Sn3d and O1s peaks after 60 min annealing contradicts the calculation. Moreover, when l H2O converts into c H2O, the EB value will decrease according to equation (5). Detailed calculation found that there is a ~0.1 eV drop of EB, which is about half of the negative chemical shift of O2 peak, when the conversion completes.…”
Section: Energy Minimization Computationmentioning
confidence: 99%
“…Having these properties, SnO2 nanostructures can be used in various constructions of chemical sensors [1][2][3], field-emission transistors [4,5], dye-based solar cells [6], optoelectronic devices etc. [7].…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al [61] have achieved nanowires inside the lithographically fabricated trenches using nanocluster source. The nanoclustered nanowires usually grow at the apex of the trench (as shown in Fig.…”
Section: Guided Self-assemblymentioning
confidence: 99%